Autonomous TGFβ signaling induces phenotypic variation in human acute myeloid leukemia. (15th February 2021) - Shingai, Yasuhiro; Yokota, Takafumi; Okuzaki, Daisuke; Sudo, Takao; Ishibashi, Tomohiko; Doi, Yukiko; Ueda, Tomoaki; Ozawa, Takayuki; Nakai, Ritsuko; Tanimura, Akira; Ichii, Michiko; Shibayama, Hirohiko; et al.
Abstract: Heterogeneity of leukemia stem cells (LSCs) is involved in their collective chemoresistance. To eradicate LSCs, it is necessary to understand the mechanisms underlying their heterogeneity. Here, we aimed to identify signals responsible for heterogeneity and variation of LSCs in human acute myeloid leukemia (AML). Monitoring expression levels of endothelial cell-selective adhesion molecule (ESAM), a hematopoietic stem cell-related marker, was useful to detect the plasticity of AML cells. While healthy human hematopoietic stem/progenitor cells robustly expressed ESAM, AML cells exhibited heterogeneous ESAM expression. Interestingly, ESAM − and ESAM + leukemia cells obtained from AML patients were mutually interconvertible in culture. KG1a and CMK, human AML clones, also represented the heterogeneity in terms of ESAM expression. Single cell culture with ESAM − or ESAM + AML clones recapitulated the phenotypic interconversion. The phenotypic alteration was regulated at the gene expression level, and RNA sequencing revealed activation of TGFβ signaling in these cells. AML cells secreted TGFβ1, which autonomously activated TGFβ pathway and induced their phenotypic variation. Surprisingly, TGFβ signaling blockade inhibited not only the variation but also the proliferation of AML cells. Therefore, autonomous activation of TGFβ signaling underlies the LSC heterogeneity, which may be a promising therapeutic target for AML. Abstract : Leukemic stem cells (LSCs) in human acute myeloid leukemia (AML) represent phenotypic variability, which is delineated by endothelial cell-selective adhesion molecule (ESAM) expression. The variable ESAM levels reflect fluctuating transcriptome in LSCs that is at least partly regulated by autocrine/paracrine cytokine signals. While autonomous TGFβ1 signaling promotes the phenotypic variability of LSCs, blocking the signaling inhibits not only their variability but also their growth by inducing apoptosis.